PERCEPTIONS OF BEGINNER VOTERS ABOUT POLITICAL RIGHTS OF CITIZENS DUE TO PARTICIPATE ON LOCAL ELECTIONS OF LAMPUNG PROVINCE - nyiayu chairunnisa; irawan suntoro; Muhamad Mona Adha (FKIP Unila, 2012)
The purposes of this research are to analyze perceptions of beginner voters about political rights of citizens, perceptions of beginner voters about local elections, and perceptions of beginner voters about political rights of citizens due to local elections at SMA Negeri 1 Bandar Lampung school year 2012/2013.This research used descriptive method, as subjects are 272 XI Grade students of SMA Negeri 1 particularly. Samples were taken for this research is 15% or 41 Students. Thedata collection usedquestionnaire technique, interview, and observation. Data were analyzed by using percentage formula. The results of research are;1. Perceptions of beginner voters about political rights of citizens at SMA Negeri 1 Bandar Lampung school year 2012/2013 are included in less understanding category, 2. Perceptions of beginner voters about local elections are included in unfavorable category, and 3. Perceptions of beginner voters about political rights of citizens due to participate on local elections at SMA Negeri 1 Bandar Lampung school year 2012/2013 stated agree.Keywords: Political rights of citizens, Local Elections.